Regulation of immunoglobulin E antibody synthesis in man by antiidiotypic antibodies. - Geha, R S (1983)
The effect of rabbit antiidiotypic antibody raised against human IgG F(ab')2 anti-tetanus toxoid (TT) antibodies on the in vitro synthesis of TT-specific IgE antibody by peripheral blood lymphocytes (PBL) was examined in three subjects. Two of these subjects were allergic twins whose sera persistently contained IgE anti-TT antibodies. The third subject was a nonallergic individual who had a slightly elevated serum IgE (250 IU/ml) and who exhibited a transient serum IgE anti-TT response after booster immunization with TT. After appropriate absorptions rabbit anti-idiotype (Id) IgG reacted with anti-TT antibodies of both IgG and IgE isotypes in an idiotype- and antigen-specific fashion. PBL and B cells from the three subjects studied spontaneously synthesized TT-specific IgE in culture. In all three cases, adsorption of B cells over plastic plates coated with anti-Id before culture specifically decreased the synthesis of IgE antibodies to TT but did not affect the synthesis of IgE antibodies to ragweed antigen E by PBL from the twin allergic subjects. Addition of anti-Id to cultures of PBL from all three subjects specifically inhibited the synthesis of TT-specific IgE. This inhibition was shown to be exerted both at the level of the B cells and via the generation of antigen-specific suppressor T cells from radiosensitive precursors. The present results indicate that the synthesis of antigen-specific IgE in man is subject to regulation by idiotypic anti-idiotypic interactions that can involve both B and T lymphocytes.